2014
DOI: 10.1128/jvi.02989-13
|View full text |Cite
|
Sign up to set email alerts
|

Global Bidirectional Transcription of the Epstein-Barr Virus Genome during Reactivation

Abstract: Epstein-Barr virus (EBV) reactivation involves the ordered induction of approximately 90 viral genes that participate in the generation of infectious virions. Using strand-specific RNA-seq to assess the EBV transcriptome during reactivation, we found extensive bidirectional transcription extending across nearly the entire genome. In contrast, only 4% of the EBV genome is currently bidirectionally annotated. Most of the newly identified transcribed regions show little evidence of coding potential, supporting no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 39 publications
(47 reference statements)
12
74
0
Order By: Relevance
“…We correlated these potential polyadenylation sites with the appearance of the RNA-seq profiles to identify sites where the read density decreased abruptly, indicating the possible presence of transcriptional termination. In addition, we searched the RNAseq data for the presence of five or more A residues which did not map to the KSHV genome, in order to identify potential polyadenylation sites, as previously described (39). We also used Northern blot analysis to map the size of each transcript in RNA isolated from cells infected with ⌬ORF57 or WT KSHV and performed 3= RACE to map the polyadenylation and cleavage sites of the mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…We correlated these potential polyadenylation sites with the appearance of the RNA-seq profiles to identify sites where the read density decreased abruptly, indicating the possible presence of transcriptional termination. In addition, we searched the RNAseq data for the presence of five or more A residues which did not map to the KSHV genome, in order to identify potential polyadenylation sites, as previously described (39). We also used Northern blot analysis to map the size of each transcript in RNA isolated from cells infected with ⌬ORF57 or WT KSHV and performed 3= RACE to map the polyadenylation and cleavage sites of the mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have found evidence for previously unknown viral long noncoding RNAs (vlncRNAs) in EBV, Kaposi's sarcoma-associated herpesvirus, MHV68, and herpes simplex virus that are expressed during the lytic cycle (4)(5)(6)(7)(8)(9). For example, evidence from our lab (9,10) and from Dresang et al (4) indicates that EBV likely expresses more than a hundred novel lytic noncoding RNAs. Further, extensive alternative splicing is observed (9,10), illustrating the existence of even greater diversity in the repertoire of expressed coding and noncoding viral transcripts during this process.…”
mentioning
confidence: 94%
“…Nevertheless, diverse roles for small noncoding RNAs (ncRNAs) are known to play important roles in EBV infection and have implications to EBV-mediated oncogenesis (2,3). Recent studies have found evidence for previously unknown viral long noncoding RNAs (vlncRNAs) in EBV, Kaposi's sarcoma-associated herpesvirus, MHV68, and herpes simplex virus that are expressed during the lytic cycle (4)(5)(6)(7)(8)(9). For example, evidence from our lab (9,10) and from Dresang et al (4) indicates that EBV likely expresses more than a hundred novel lytic noncoding RNAs.…”
mentioning
confidence: 99%
“…In order to return both primary and secondary alignments, use the following commands: 19. Note that abundant unannotated transcription has been detected in EBV during reactivation [8].…”
Section: Notesmentioning
confidence: 99%